Poverty Reduction and Pro-poorness Growth in Bihar and Jharkhand: A Comparative Analysis. - Kumar Sinha, Jitendra (Journal of Advanced Research in Economics and Business Management, 2023)
This study compares poverty reduction and pro-poorness of growth in rural and urban areas of Bihar, Jharkhand, and of all India. Bihar has recorded faster poverty reduction during 2004-05 and 2011-12 in compassion to Jharkhand and all-India. An increasing trend was witnessed in growth inequality at all Indian levels, but a reverse declining trend was witnessed in Bihar. Further, growth inequality has decreased in rural areas of Bihar and Jharkhand but increased in urban areas. The positive value of inequality elasticity at the all-India level simply implies that poverty alleviation programs did not adequately benefit poor people. The inequality elasticity was negative in both the rural and urban sectors of Bihar and the urban sector of Jharkhand implying that the lower strata have benefitted more than the upper-income group. A larger reduction in inequality in both rural and urban areas suggests that Bihar implemented more effective pro-poor programs than Jharkhand. Surprisingly, the inequality elasticity was positive in the rural sector of Jharkhand implying that programs did not benefit adequately rural people in Jharkhand. The poverty reduction impact on the growth of income measured by poverty elasticity of growth remains the same for both Bihar and Jharkhand. However, Bihar witnessed faster poverty reduction due to the effectiveness of anti-poverty measures and welfare spending, reflected by higher efficiency in reducing poverty in the decomposition of annual change in poverty.